Pemberdayaan Ekonomi Melalui Integrated Farming di dalam Pondok Pesantren Nasyrul ‘Ulum - Akbar Setia Budi; Andri Juniarta; Asta Gilang Patria; Lilis Renfiana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
As a religious institution, Islamic boarding schools have enormous potential in advancing prosperity and economic development. They also have a significant impact on the daily lives of the students who attend. Therefore, the Nasyrul 'Ulum Islamic boarding school which is located at Tempuran 12a Central Lampung created an integrated agricultural business unit to advance its welfare and economic development. The purpose of this research is to describe and evaluate the following things: the steps in establishing an integrated agricultural business unit (IFB) in Islamic boarding schools, the business unit carried out is catfish cultivation, where waste from food or leftovers from students is made into catfish feed and catfish wastewater are used as organic plant fertilizer; the results of this process for the economy of these schools; and factors that facilitate or hinder the growth of the Islamic boarding school economic trend. Researchers use a qualitative approach to answer the problem formulation. Research findings show that the Islamic boarding school's efforts to develop its economy through integrated agricultural business units have succeeded in increasing the boarding school's income and creating jobs for the community around the boarding school and especially alumni of the Nasyrul 'Ulum Islamic boarding school and how many jobs are available in accordance with the amount of effort made, source available resources, and the extent to which the community is involved in the program. Apart from creating jobs, it can also increase the knowledge, skills and experience of both local communities and students in the agricultural sector. Especially in the field of fisheries cultivation.